Thunderstorm Electrification - Bradshaw, Stephanie Marie (Proceedings of the Wisconsin Space Conference, 2016)
Understanding how thunderstorms work is important as it can help assess risks associated with electrical activity in thunderstorms and electrical activity in other areas such as volcanic eruptions, heavy snowstorms, and large hurricanes. We studied the electrification processes in thunderstorms by investigating literature resources to understand what was known about the electrification processes in thunderstorms. The electrification processes were then studied by investigating what observations could be made using CAERENet (Carthage Atmospheric Electricity Research and Education Network) electric field mills to better understand how thunderstorms electrify. In order to understand what could be observed about thunderstorm electrification with an electric field mill, we built mathematical models of electric charge, current, and electric field using Python. A comparison between model data and electric field mill data will be used to better understand electrification processes in a naturally occurring thunderstorm.